# How do you factor 125x 3?

## How do you factor 125x 3?

Rewrite 125 as 53 . Since both terms are perfect cubes, factor using the difference of cubes formula, a3−b3=(a−b)(a2+ab+b2) a 3 – b 3 = ( a – b ) ( a 2 + a b + b 2 ) where a=5 and b=x . Raise 5 to the power of 2 .

How do you factor 125×3 27?

1. 125×3−27 is a difference of cubes.
2. 125×3=(5x)3⇒a=5x.
3. 27=(3)3⇒b=3.

What is the complete factorization of 3x 4 48?

3×4 – 48 = 3(x2 + 4)(x – 2)(x + 2). There are 2 terms and there is a common factor of 2. Then the expression in the brackets is the difference of 2 cubes. Remember how to factor a3 – b3.

### How do you factor 125?

Factors of 125

1. Factors of 125: 1, 5, 25, 125.
2. Prime Factorization of 125: 5 × 5 × 5.

How do you factor 8x 3 y 3?

Algebra Examples Rewrite 8×3 8 x 3 as (2x)3 ( 2 x ) 3 . Since both terms are perfect cubes, factor using the difference of cubes formula, a3−b3=(a−b)(a2+ab+b2) a 3 – b 3 = ( a – b ) ( a 2 + a b + b 2 ) where a=2x a = 2 x and b=y . Simplify. Apply the product rule to 2x 2 x .

How do you factor 49×2 9?

Algebra Examples Rewrite 49×2 49 x 2 as (7x)2 ( 7 x ) 2 . Rewrite 9 as 32 . Since both terms are perfect squares, factor using the difference of squares formula, a2−b2=(a+b)(a−b) a 2 – b 2 = ( a + b ) ( a – b ) where a=7x a = 7 x and b=3 .

#### How to write factor 125 as 53 5 3?

Rewrite 125 125 as 53 5 3. Since both terms are perfect cubes, factor using the difference of cubes formula, a3 −b3 = (a−b)(a2 + ab+b2) a 3 – b 3 = ( a – b) ( a 2 + a b + b 2) where a = x a = x and b = 5 b = 5. Simplify.

How to factor a third power trinomial?

Factor a third power trinomial (a polynomial with three terms) such as x 3+5x 2+6x. Think of a monomial that is a factor of each of the terms in the equation. In x 3+5x 2+6x, x is a common factor for each of the terms.

What do you call a third power polynomial?

A third power polynomial, also called a cubic polynomial, includes at least one monomial or term that is cubed, or raised to the third power.